Pengaruh Karakteristik Dewan Direksi Terhadap Pengambilan Risiko Dengan Direktur Independen Sebagai Variabel Moderasi - Thalia Nur Apriaseli; Suwarno Suwarno (Universitas Muhammadiyah Gresik, 2022)
This study aims to examine the effect of board directors characteristics on risk taking with independen directors as moderating variable. The population used is Trade, Service, and Investment for period 2018-2020. The data analysis technique used Moderate Regression Analysis. Sampling using purposive sampling method and obtained as many as 37 companies. Based on the research results gender diversity has no effect on risk taking, CEO tenure has positive effect on risk taking, and CEO education has no effect on risk taking. Based on research independent directors as moderate variable has moderate effect gender diversity on risk taking, independent directors has moderate effect CEO tenure on risk taking, and independen directors cannot moderate effect CEO education on risk taking.